Redesigning a food supply chain for environmental sustainability – An analysis of resource use and recovery. (1st January 2020) - Krishnan, Ramesh; Agarwal, Renu; Bajada, Christopher; Arshinder, K.
Abstract: Food supply will need to increase by around 70% from its current levels in order to meet the world population growth of 9.6 billion by 2050. Food waste is the biggest challenge in global food security, wherein approximately 20–30% of food waste occurs in the post-harvest stage of the food supply chain (FSC) in developing countries. This food waste generates significant negative environmental effects in addition to the unnecessary usage (and wastage) of resources consumed in producing the wasted food. Whilst India is the major producer and exporter of many agricultural crops, there is a lack of research that evaluates the environmental impact of the Indian FSCs. The environmental impact of the same product varies according to the resources consumed and so it is important that the environmental impact of individual supply chains be considered. Also, there is a lack of studies that uses the result of environmental impact assessment to identify the operational and resource inefficiencies in FSC and develop a framework for sustainable FSC. Thus, this study aims to identify operational and resource inefficiencies present in FSC through environmental impact assessment and propose a framework for redesigning the FSC to improve environmental sustainability. Life cycle assessment approach is used for assessing the environmental impact. This framework has been applied to a mango food supply chain. Highlights: Assessed the environmental impact of the Indian mango food supply chain (FSC). Identified operational and resource inefficiencies in Indian mango FSC. Proposed a framework for redesign of FSC for environmental sustainability. Opportunity for reducing environmental impact is showed using sensitivity analysis.